Strategi Organisasi Pendidikan di Tingkat Sekolah Menengah dalam Menghadapi Tantangan Global - Alya Fatma Hadi; Fatimah Az-Zahra; Nadiya Salsabila (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
Educational organization strategy is the most important element in facing global challenges at the secondary school level. In an increasingly complex era of globalization, secondary schools are expected to be able to produce graduates who are competent and ready to face the demands of the rapidly changing world of work. This article was created to find out and analyze how the strategy of educational organizations at the secondary school level in facing global challenges. This research uses a qualitative approach with a descriptive method research type sourced from literature studies. Literature study is one of the research methods that uses the results of reviews from other journals as a source of reference. From the results it is known that: (1) Educational organization must be well implemented in secondary schools in line with the times. (2) It is important for education to be integrated with strategic management that ensures that educational goals and long-term vision are achieved. (3) Education as an organization also needs compact cooperation between the community and the government to build synergy between educational institutions.